Oral contraceptive use and survival in women with invasive breast cancer - Lu, Yani (2011)
BACKGROUND: Oral contraceptives (OCs) are widely used in the U.S. Although the relation between OC use and breast cancer incidence has been widely studied, the few studies examining associations between OC use prior to breast cancer diagnosis and survival are inconsistent. METHODS: Women with invasive breast cancer participating in the Women's Contraceptive and Reproductive Experiences (CARE) Study, a population-based case-control study (4565 women ages 35–64 years), and the California Teachers Study (CTS) cohort (3929 women ages 28–91 years) were followed for vital status. 1064 women died in the CARE Study (median follow-up, 8.6 years) and 523 died in the CTS (median follow-up, 6.1 years). Cox proportional hazards regression provided hazard rate ratio estimates (RRs) with 95% confidence intervals (CIs) for risk of death from any cause and from breast cancer. RESULTS: No association was observed for any OC use prior to diagnosis and all-cause mortality (CARE Study: RR=1.01 (95% CI=0.86–1.19); CTS: RR=0.84 (95% CI=0.67–1.05)). A decreased risk of all-cause mortality was observed in the CTS among women with more than 10 years of OC use (RR=0.67, 95% CI=0.47–0.96); however, no trend of decreasing risk with increasing OC duration was observed (P-trend=0.22), and no association was observed in the CARE study. No associations were observed for breast cancer-specific mortality. CONCLUSIONS: OC use is not associated with all-cause or breast cancer-specific mortality among women with invasive breast cancer. IMPACT: These two independent studies demonstrated no overall association between OC use and survival among women with breast cancer.